Relativity Simply Explained
One of the clearest, most entertaining introductions to the subject ever written offers lucid explanations of not only the special and general theories of relativity, but also of the Michelson-Morley experiment, gravity and spacetime, Mach?s principle, the twin paradox, models of the universe and other topics. ...by far the best layman?s account of this difficult subject.?Christian Science Monitor. 100 two-color illustrations.